Communal nesting differentially attenuates the impact of pre-weaning social isolation on behavior in male and female rats during adolescence and adulthood - Bratzu, Jessica; Ciscato, Maria; Pisanu, Augusta; Talani, Giuseppe; Frau, Roberto; Porcu, Patrizia; Diana, Marco; Fumagalli, Fabio; Romualdi, Patrizia; Rullo, Laura; Trezza, Viviana; Ciccocioppo, Roberto; et al. (Frontiers in Behavioral Neuroscience, 2023)
Early social isolation (ESI) disrupts neurodevelopmental processes, potentially leading to longlasting emotional and cognitive changes in adulthood. Communal nesting (CN), i.e., the sharing of parental responsibilities between multiple individuals in a nest, creates a socially enriching environment known to impact social and anxiety-related behaviors. This study examines the effects of (i) the CN condition and of (ii) ESI during the 3 rd week of life (i.e., pre-weaning ESI) on motor, cognitive, and emotional domains during adolescence and adulthood in male and female rats reared in the two different housing conditions, as well as (iii) the potential of CN to mitigate the impact of ESI on offspring. We found that in a spontaneous locomotor activity test, females exhibited higher activity levels compared to males. In female groups, adolescents reared in standard housing (SH) condition spent less time in the center of the arena, suggestive of increased anxiety levels, while the CN condition increased the time spent in the center during adolescence, but not adulthood, independently from ESI. The prepulse inhibition (PPI) test showed a reduced PPI in ESI adolescent animals of both sexes and in adult males (but not in adult females), with CN restoring PPI in males, but not in adolescent females. Further, in the marble burying test SH-ESI adolescent males exhibited more marble burials than all other groups, suggestive of obsessive-compulsive traits. CN completely reversed this stress-induced effect. Interestingly, ESI and CN did not have a significant impact on burying behavior in adult animals of both sexes. Overall, our findings (i) assesses the effects of ESI on locomotion, sensorimotor gating, and compulsive-like behaviors, (ii) reveal distinct vulnerabilities of males and females within these domains, and (iii) show how early-life social enrichment may successfully counteract some of the behavioral alterations induced by earlylife social stress in a sex-dependent manner. This study strengthens the notion that social experiences during early-life can shape emotional and cognitive outcomes in adulthood, and points to the importance of social enrichment interventions for mitigating the negative effects of early social stress on neurodevelopment.